A novel extracellular glycosidase activity from Rhodotorula mucilaginosa: its application potential in wine aroma enhancement. (February 2016) - Hu, K.; Zhu, X.L.; Mu, H.; Ma, Y.; Ullah, N.; Tao, Y.S.
Abstract: The aim of the work was to evaluate the application potential of a glycosidase extract of one indigenous non‐ Saccharomyces strain in wine aroma enhancement. The isolate was selected from a local winemaking region in China for its high β ‐glucosidase level and was identified as Rhodotorula mucilaginosa . The tolerance of the glycosidase extract to the typical winemaking conditions was assessed using the activity of its β ‐glucosidase. After that, the hydrolysis capacity of R. mucilaginosa glycosidase for liberation of grape aroma glycosides was characterized in comparison to commercial enzyme preparations. Results of this work revealed that glycosidase extract from R. mucilaginosa proved to be active in the presence of 0–20% (w/v) glucose, 0–20% (v/v) ethanol and at pH 3·0–5·0. In the hydrolysis of aroma precursors, enzymes obtained from different origins possessed various levels of specificity and activity, showing high origin dependence ( α  = 0·05). Compared to commercial enzymes, the indigenous R. mucilaginosa glycosidase extract presented better catalytic preference for the 'fruity and floral' glycosides of benzenic compounds and C13 ‐norisoprenoids, but less sensitivity to the glycosides of C6 compounds and volatile phenols. Significance and Impact of the Study: This work presents a novel extracellular glycosidase preparation from an indigenous Rhodotorula mucilaginosa strain selected from a local winemaking region in China. This enzyme extract exhibits strong tolerance towards winemaking conditions. It shows hydrolysis specificity for glycosides of benzenic compounds and C13 ‐norisoprenoids, proving a potential candidate for improving floral and fruity aroma characteristics of wine. Abstract : Significance and Impact of the Study: This work presents a novel extracellular glycosidase preparation from an indigenous Rhodotorula mucilaginosa strain selected from a local winemaking region in China. This enzyme extract exhibits strong tolerance towards winemaking conditions. It shows hydrolysis specificity for glycosides of benzenic compounds and C13 ‐norisoprenoids, proving a potential candidate for improving floral and fruity aroma characteristics of wine.